The identity of the oriental leafhopper genera Cyrta Melichar and Placidus Distant (Hemiptera: Cicadellidae: Stegelytrinae), with description of a new genus - Wei, Cong; Webb, M. D.; Zhang, Yalin (Zootaxa, 2008)
The identities of the Oriental leafhopper genera Cyrta Melichar and Placidus Distant are reviewed, and Cyrta is placed as a senior synonym of Placidus. The following new combinations and new species are proposed for Cyrta: C. brunnea (Kuoh) comb. n.; C. dentata (Zhang & Wei) comb. n.; C. flosifronta (Zhang & Wei) comb. n.; C. furcata (Li & Zhang) comb. n.; Cyrta hornei (Distant) comb. n.; C. incurvata (Wei & Zhang) comb. n.; C. longwanshensis (Li & Zhang) comb. n.; C. nigrocupulifera (Zhang & Wei) comb. n.; C. orientalis (Schumacher) comb. n.; C. striolata (Zhang & Wei) comb. n.; C. testacea (Kuoh) comb. n.; C. vicina (Dlabola) comb. n.; C. tiantaishanensis sp. n.; C. spinosa sp. n.; C. conduplicata sp. n.; C. coalita sp. n. and C. fujianensis sp. n. A new genus, Paracyrta gen. n., is erected to accommodate the following species previously included in Cyrta: P. blattina (Jacobi) comb. n.; P. recusetosa (Zhang & Wei) comb. n.; P. setosa (Zhang & Sun) comb. n.; P. banna (Zhang & Wei) comb. n.; P. bicolor (Zhang & Wei) comb. n.; P. longiloba (Zhang & Wei) comb. n.; P. dentata (Zhang & Wei) comb. n.; P. bimaculata (Zhang & Sun) comb. n.; P. parafrons (Zhang & Wei) comb. n. A key is provided for the above species of Cyrta and the relationship between Cyrta and Paracyrta and other Oriental stegelytrine genera is given. The host plants and mud-puddling behaviour of the representatives of this subfamily are discussed.